Analyzing the biosynthetic potential of antimicrobial-producing actinobacteria originating from Indonesia - Anissa Utami; Pamela Apriliana; Dewi S. Zilda; Zidny Ilmiah; Puspita Lisdiyanti; Siswa Setyahadi; Yudi Kusnadi; Agustinus R. Uria (Indonesian Journal of Biotechnology, 2021)
We investigated the biosynthetic potential of soil-associated actinobacteria originating from Indonesia, identified as Streptomyces luridus and as Streptomyces luteosporeus. Antimicrobial assays indicated inhibitory activity by both strains against the pathogen Pseudomonas aeruginosa, with S. luteosporeus particularly inhibiting the growth of Bacillus subtilis. PCR-amplification, cloning, and sequencing of ketosynthase (KS) domains of type I modular polyketide (PKS-I) and adenylation (AD) domains of non-ribosomal peptide synthetase (NRPS) indicated the diversity of KS and AD domains derived from both Indonesian Streptomyces. Further phylogenetic analysis showed that KS domains from the subclass cis-AT PKS can be classified as being a part of a loading module or an extension module, along with their predicted substrate specificity. The results suggest that both strains are a potential source of novel biosynthetic pathways. This genetic analysis approach can be used as a fast guide to obtain insight into natural product biosynthetic gene diversity in microorganisms.